A particular ankle fracture: destot fracture with a fibular shaft fracture - Rhita Salah; Amine El Ghazoui (PAMJ Clinical Medicine, 2020)

(untitled)
A 39 year-old police officer, without medical history, was referred to the emergency departement showing an ankle injury, following a police chase. The left foot was twisted outwards and abducted. The mechanism of injury was then an ankle eversion. Symptoms were pain on attempting to walk, swelling and there were no malposition of the joint nor open wound. Medial malleolus was gently palpated and no bone pain was present. However, there was a tenderness to pressure over the lateral and posterior malleoli. Ankle mobilization was possible, although slightly painful. The posterior tibial and dorsalis pedis pulses were palpable and capillary refill time was under 3 seconds. Further associated bone injuries could be ruled out by palpation of the ipsilateral knee, proximal head of the fibula and tarsal bones. We ended our physical evaluation with a nerve examination which showed no sensory-motor deficit. As we suspected a fracture, standard x-ray imaging of the left ankle joint was performed in two directions, anteroposterior and lateral. They showed a posterior malleolus fracture also known as Destot fracture, with moderate posterior displacement, and a non displaced fracture of the middle third of fibular shaft with butterfly fragment. There was no roentgenographic evidence of tibiofibular diastasis, and the medial malleolus was intact. Moreover, radiological evaluation of the ipsilateral knee and foot was performed and did not show any further associated fractures. Treatment consisted in a below-the-knee non-weight-bearing plaster cast for six weeks. A good anatomical, roentgenographic, and functional result was obtained.